Chen, C. J. & Toh, S. C. (2005). A feasible instructional development model for virtual reality (VR)-based learning environments: Its efficacy in the novice car driver instruction of Malaysia. - Chen, Chwen Jen; Seong, Chong Toh (Springer, 2005)
This article focuses on the instructional design process of a nonimmersive virtual reality (VR)-based learning environment. The learning environment is intended to complement the current novice car driver instruction program, focusing solely on cognitive skills, in Malaysia. This article elaborates on how we designed and developed the learning environment based on a relatively new constructivist instructional model, the reflective, recursive design and development (R2D2) model (Willis, 1995; Willis & Wright, 2000). We describe the design and development processes of the various components of the learning environment into the single-path prototype, and later to the alpha, and beta versions, based on three guiding principles (a) recursive, nonlinear design; (b) reflective design; and (c) participatory design. This article also highlights the experience that we foresee as useful or transferable for future design and development efforts. More important, the development of this learning environment provides evidence on the feasibility of employing a constructivist instructional model to guide the instructional design process of VR-based learning environments.